2010
DOI: 10.1111/j.1744-7917.2010.01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Grasshoppers (Orthoptera: Acrididae) select vegetation patches in local‐scale responses to foliar nitrogen but not phosphorus in native grassland

Abstract: Key elements such as nitrogen (N) and phosphorus (P) are often limiting relative to the nutritional needs of herbivores that feed on them. While N often limits insect herbivores in natural terrestrial ecosystems, the effect of P is poorly studied in the field, even though compelling hypotheses from the ecological stoichiometry literature predict its importance. We evaluated small‐scale spatial distributions of, and herbivory by, grasshoppers among neighboring plots that vary in foliar‐N and ‐P in tallgrass pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 89 publications
8
15
1
Order By: Relevance
“…The ability of grasshoppers to obtain adequate P by foraging occasionally on high-P plants, and the negative effects of high-P diets, may explain why N but not P fertilization has been shown to affect grasshopper population densities in central North American grasslands, despite the observation that average foliar P concentrations available were in the range of those shown to be limiting to growth in this study (Loaiza et al, 2011). However, Joern et al (2012) found that plant P content was the most important element predicting overall grasshopper abundance in the central Nebraskan grasslands.…”
Section: Relevance For Field Conditionscontrasting
confidence: 44%
“…The ability of grasshoppers to obtain adequate P by foraging occasionally on high-P plants, and the negative effects of high-P diets, may explain why N but not P fertilization has been shown to affect grasshopper population densities in central North American grasslands, despite the observation that average foliar P concentrations available were in the range of those shown to be limiting to growth in this study (Loaiza et al, 2011). However, Joern et al (2012) found that plant P content was the most important element predicting overall grasshopper abundance in the central Nebraskan grasslands.…”
Section: Relevance For Field Conditionscontrasting
confidence: 44%
“…Second, grasshopper population densities fluctuate greatly in time or space, and communities vary in species composition at both local and regional scales (Joern and Gaines 1990, Lockwood 1997, Jonas and Joern 2007. Third, grasshopper densities or species compositions on a local scale are distributed spatially in a way that may reflect spatial heterogeneity in food quality (Heidorn and Joern 1987, White 1993, Haddad et al 2001, Loaiza et al 2011. We ask three primary questions: (1) How variable are plant foliar elemental concentrations between grasses and forbs, and between sites?…”
Section: Introductionmentioning
confidence: 99%
“…Lower N availability can limit feed efficiency by reducing urea recycling and microbial efficiency in ruminants (Reed 1995) as reported for other forages containing CT (Mangan 1988). In grasshoppers, lower N availability is associated with reduced population densities because N is a limiting nutrient (Loaiza et al 2011). Additionally, N availability is a major driver of foliar damage by grasshoppers (Loaiza et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In grasshoppers, lower N availability is associated with reduced population densities because N is a limiting nutrient (Loaiza et al 2011). Additionally, N availability is a major driver of foliar damage by grasshoppers (Loaiza et al 2011).…”
Section: Discussionmentioning
confidence: 99%